DYSTOCIA DUE TO SECONDARY UTERINE INERTIA IN A GERMAN SHEPHERD BITCH - Kumar, Pravesh; Sharma, Amit; Barman, Purabi; Singh , Madhumeet (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
A case of dystocia in German Shepherd bitch due to secondary uterine inertia and its treatment with oxytocin is reported.